Pengembangan adaptive mobile learning pada mata pelajaran biologi SMA sebagai upaya mendukung proses blended learning - Ence Surahman; Herman Dwi Surjono (Jurnal Inovasi Teknologi Pendidikan, 2017)
Penelitian ini bertujuan untuk: (1) menghasilkan produk Adaptive Mobile Learning yang layak menurut ahli materi, ahli media dan pengguna, (2) mengetahui kebermanfaatan produk melalui ketuntasan hasil belajar peserta didik, dan kemampuan program untuk mendukung blended learning. Penelitian pengembangan ini mengikuti langkah-langkah yang dikembangkan oleh Alessi dan Trollip yang terdiri dari tiga tahap, yakni perencanaan, perancangan, dan pengembangan. Produk awal divalidasi oleh ahli media dan ahli materi kemudian dilakukan revisi. Tahap berikutnya dilakukan tes beta 1 terhadap beberapa calon pengguna, dan diujicobakan kepada 29 pengguna. Selanjutnya tes sumatif terhadap 29 peserta didik. Hasil penelitian menunjukkan bahwa: (1) produk Adaptive Mobile Learning dinyatakan layak sebagai media pembelajaran berdasarkan validasi ahli materi, ahli media, dan pengguna dengan rerata kelayakan mencapai skor 3,35 dengan kategori “sangat baik”; (2) kebermanfaatan produk dibuktikan melalui perbedaan hasil belajar mencapai angka kenaikan sebesar 33,80 sesudah menggunakan produk Adaptive Mobile Learning dan terbukti mendukung blended learning dengan skor 3,42 dengan kategori “sangat baik”.Kata kunci: adaptive learning, mobile learning, blended learning. THE DEVELOPING OF ADAPTIVE MOBILE LEARNING IN SENIOR HIGH SCHOOL BIOLOGY SUBJECT AS EFFORTS TO SUPPORT THE PROCESS OF BLENDED LEARNINGAbstractThis research study aims: (1) producing Adaptive Mobile Learning which fulfil the criteria and appropriateness according to the experts, media experts, and users; and (2) the usefulness of the product seen from the completeness of the student learning outcomes and ability the product to support blended learning process. This research and development study refers to the stages developed by Alessi and Trollip which classified into three stages namely planning, designing, and developing. Early product was validated by the media and experts (alpha test), followed by revision. The next stage namely beta 1 test was done by some users and then tested by the 29 students as the users of the product. After that, a summative test was administered to them. The result of the study shows that: (1) the product namely Adaptive Mobile Learning fulfils the criteria and has been claimed as appropriate to be used as learning media according to the validation from the materials experts, media experts, and students who use the product with the average appropriateness score of 3.35 which belongs to the category of “very good”; and (2) the usefulness of the product is confirmed by the difference of the results of the last and early tests, that of after and before the use of the product of Adaptive Mobile Learning with raise the score of 33,80 after use the product, and that it supports the process of blended learning with the average appropriateness score of 3,42 which belongs to the category “very good”.Keywords: adaptive learning, mobile learning, blended learning